Experimental research and mechanism analysis on chloride ingress at different concrete zone along altitude in marine environment. Part 1. Moisture distribution. (20th August 2018) - Zhang, Linglei; Ji, Yong-sheng; Gao, Furong; Liu, Lili; Li, Jun
Highlights: The net amount of water absorption during each cycle gradually drops and eventually reaches an equilibrium state. Both IDMTs at submerged and atmospheric zones are zero. Length of IDMT at the splash zone is about 20 mm, and StMC within the concrete equals EMC. The IDMT determines the transport depth of chloride by absorption, and the CWAA determines the amount of chloride absorbed into concrete. The CWAA reaches to the maximum at the highest point of the tide, and at this point the penetration of chloride ions also reaches its maximum rate. Abstract: The moisture distributions in concrete of different zones are different in marine environment. The variations of moisture distribution during drying and wetting were analyzed in this paper. A laboratory test system that whole piece of real concrete was subjected to an environment close to the real marine environment was developed and used to simulate the real marine environment, by which the variations of moisture distribution in concrete of different zones along elevated altitude were studied. The test results reveal that the influential depth of moisture transport (IDMT) and the stability moisture content (StMC) in concrete of different zones are variable. The IDMTs in concrete of splash and tidal zones are larger than those of other zones. IDMT changes along elevated altitude, and the peak value of IDMT appears near the top water line of tidal zone which is the key region of durability design and maintenance.